Spotted cucumber beetle (Diabrotica undecimpunctata howardi) is attracted to vittatalactone, the pheromone of striped cucumber beetle (Acalymma vittatum) - Ariela I. Haber; Kayla Pasteur; Filadelfo Guzman; Sean M. Boyle; Thomas P. Kuhar; Donald C. Weber (Journal of Pest Science, 2023)
Spotted cucumber beetle ( Diabrotica undecimpunctata howardi ; also known as southern corn rootworm) is a pest feeding on many crops, including cucurbits, corn (maize), peanuts, beans, and other crops and wild plants in North America. On cucurbit crops, where it co-occurs with striped cucumber beetle ( Acalymma vittatum ), both are key pests that vector Erwinia tracheiphila, a destructive pathogen that causes bacterial wilt. Here we deployed synthetic vittatalactone, the male-produced aggregation pheromone of A. vittatum , as lures in the field, to measure attraction of the target and non-target insects. Both sexes of D. u. howardi were strongly attracted to the vittatalactone lures (5–7.5-fold compared to blank trap) throughout the growing season in Maryland and Virginia, USA. Moreover, D. u. howardi was more attracted to live A. vittatum males feeding on squash plants than to plants with females or without any beetles, confirming the genuine organismal cross-attraction between these two key pests. The kairomonal attraction to vittatalactone suggests that it functions as a “keystone semiochemical,” mediating the colonization of cucurbits by multiple herbivore species. Such cross attraction could allow for use of vittatalactone in management of multiple pest species, with potential reduction of pesticide use in cucurbit crops.